Exterior material for power storage device and power storage device using the same
The exterior material for storage devices, featuring a substrate, metal foil, thermal fusion resin, and slide layer, addresses the issue of slipping and cracking at high temperatures, ensuring structural integrity and preventing water ingress, thus improving device performance.
Patent Information
- Application Number
- JP2023119634
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
Existing exterior materials for lithium-ion batteries and all-solid batteries face issues with cracking and slipping at high temperatures, especially when subjected to pressure and vibration, which can lead to water ingress and reduced performance.
An exterior material comprising a substrate layer, metal foil layer, thermal fusion resin layer, and a slide layer with a specific static friction coefficient, designed to reduce slipping and cracking at high temperatures by incorporating a slide layer that enhances static friction.
The exterior material effectively suppresses slipping and cracking, maintaining structural integrity and preventing water ingress, even under high temperature and pressure conditions, thereby enhancing the performance and reliability of storage devices.
Smart Images

Figure 2025016869000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an exterior material for an electricity storage device and an electricity storage device using the same. [Background technology]
[0002] Known examples of power storage devices include secondary batteries such as lithium ion batteries, nickel metal hydride batteries, and lead storage batteries, as well as electrochemical capacitors such as electric double layer capacitors. Due to the miniaturization of portable devices or the limitations of installation space, there is a demand for further miniaturization of power storage devices, and lithium ion batteries with high energy density have attracted attention. Metal cans have traditionally been used as exterior materials for lithium ion batteries, but multilayer films that are lightweight, have high heat dissipation properties, and can be produced at low cost have come to be used.
[0003] A lithium-ion battery that uses the above multilayer film as an exterior material is called a laminated lithium-ion battery. The exterior material covers a battery cell having a positive electrode, a separator, a negative electrode, an electrolyte, etc., and prevents moisture from penetrating into the battery. A laminated lithium-ion battery is manufactured, for example, by forming a recess in part of the exterior material by cold forming, housing a battery cell in the recess, folding back the remaining part of the exterior material, and heat sealing the edges (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-101765 A Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, research and development of a power storage device called an all-solid-state battery is being carried out as a next-generation battery of lithium-ion batteries. An all-solid-state battery is characterized by using a solid electrolyte instead of an organic electrolyte solution as an electrolyte. While a lithium-ion battery cannot be used at temperatures higher than the boiling point temperature of the electrolyte solution (about 80°C), an all-solid-state battery can be used at temperatures exceeding 100°C, and the conductivity of lithium ions can be increased by operating the battery under high temperature conditions (for example, 100 to 150°C). In addition, when an all-solid-state battery is used, the space and cost required for a cooling system for cooling the battery can be reduced.
[0006] However, such multilayer films may suffer from cracks or breaks when recesses are formed by cold forming, and there is still room for improvement in terms of formability.
[0007] Furthermore, such multilayer films are sometimes used as exterior containers for all-solid-state batteries, in which case battery cells are housed in the exterior container and held in a pressurized state via the multilayer film. However, all-solid-state batteries are prone to high temperatures of 40°C or higher during operation, and if they are subjected to vibrations or the like at that time, the battery cells may slip relative to the multilayer film inside the exterior container. Therefore, the exterior materials for all-solid-state batteries are required to be less likely to slip relative to the battery cells even when the battery cells are placed in a high-temperature environment of 40°C or higher while being pressurized.
[0008] In addition to all-solid-state batteries, other power storage devices such as lithium ion capacitors that can be used at high temperatures are being developed. Therefore, the exterior materials of other power storage devices such as lithium ion capacitors are also required to be less likely to slip on the battery cells even when the battery cells are placed in a high-temperature environment of 40°C or higher with pressure applied to the battery cells.
[0009] The present disclosure has been made in consideration of the above-mentioned problems, and aims to provide an exterior material for an energy storage device that has excellent formability and is capable of suppressing slippage against a battery cell even when the battery cell of the energy storage device is placed in an environment of 40°C or higher while being pressurized, and an energy storage device using the same. [Means for solving the problem]
[0010] In order to solve the above problems, one aspect of the present disclosure is an electrical storage device packaging material including a base material layer, a barrier layer including a metal foil layer, and a thermal adhesive resin layer in this order, the electrical storage device packaging material including a lubricant layer including a lubricant on a surface of the thermal adhesive resin layer, the thermal adhesive resin layer taking in the lubricant from the lubricant layer when the electrical storage device packaging material is placed in an environment of 40° C. or higher, and the amount of the lubricant layer is 10 mg / m 2 The present invention provides an exterior material for an electricity storage device that can achieve the following:
[0011] The electrical storage device exterior material has a lubricant layer containing a lubricant on the surface of the heat-sealed resin layer. Therefore, when a recess is formed in the exterior material from the lubricant layer side using a mold, the mold easily slides on the lubricant layer, reducing the static friction coefficient that the mold exerts on the exterior material, and the exterior material is less likely to break or crack. Therefore, the electrical storage device exterior material has excellent moldability. Furthermore, after the molding process for the electrical storage device exterior material is completed, when the electrical storage device exterior material is placed in an environment of 40°C or higher, the thermally sealed resin layer takes in the lubricant from the lubricant layer, and the amount of the lubricant layer increases to 10 mg / m. 2 For this reason, for example, after placing the exterior material in an environment of 40°C or higher, a battery cell of an electricity storage device is placed between two exterior materials with the lubricant layer facing the battery cell side, and when pressure is applied to the battery cell via the exterior material, the lubricant contained in the lubricant layer is already incorporated into the heat-sealed resin layer, and the amount of the lubricant layer is increased to 10 mg / m. 2 Since the static friction coefficient of the exterior material against the battery cell is large, it is possible to suppress slippage of the exterior material against the battery cell.
[0012] In the packaging material for an electricity storage device, it is preferable that the heat-sealable resin layer includes a sealant layer, and the content of a lubricant in the heat-sealable resin layer is less than 200 ppm by mass. In this case, when the exterior material for an electricity storage device is placed in an environment of 40° C. or higher, the sealant layer can effectively absorb the lubricant from the lubricant layer. For this reason, for example, after placing the exterior material in an environment of 40° C. or higher, if a battery cell of the electricity storage device is placed between two exterior materials with the lubricant layer facing the battery cell side and pressure is applied to the battery cell via the exterior material, the static friction coefficient of the exterior material against the battery cell becomes larger, and slippage of the exterior material against the battery cell can be more sufficiently suppressed.
[0013] In the packaging material for an electricity storage device, it is preferable that the heat-sealable resin layer includes a sealant layer, and the heat-sealable resin layer includes a polyolefin resin. In this case, the heat sealability of the sealant layer of the heat-sealable resin layer is improved and the moisture permeability is likely to be reduced, so that the packaging material can have high heat sealability and barrier properties.
[0014] In the exterior packaging material for an electricity storage device, the lubricant contained in the lubricant layer may be a fatty acid amide.
[0015] In the exterior packaging material for an electricity storage device, the lubricant layer is preferably obtained by coating a composition containing the lubricant. Since the lubricant layer is obtained by coating a composition containing a lubricant, the amount of the lubricant layer is easy to control. Therefore, the amount of the lubricant layer is set to 10 mg / m2, which exhibits excellent moldability. 2 Since the lubricant layer is obtained by coating a composition containing a lubricant, the amount of the lubricant layer can be made equal to or less than the amount of the lubricant that can be incorporated into the heat-sealable resin layer.
[0016] In the packaging material for an electricity storage device, the surface of the heat-sealable resin layer on the side of the lubricant layer preferably has a surface roughness Sa of 1.0 μm or less. The surface roughness Sa of the surface of the heat-sealable resin layer on the lubricant layer side also affects the ease of slipping of the mold. If the surface roughness Sa of the surface of the heat-sealable resin layer on the lubricant layer side is 1.0 μm or less, the contact area between the exterior material and the battery cell can be increased after the lubricant contained in the lubricant layer is incorporated into the heat-sealable resin layer, making it difficult for the exterior material to slip against the battery cell.
[0017] The exterior packaging material for an electricity storage device may further include an adhesive layer between the base layer and the barrier layer.
[0018] In the packaging material for an electricity storage device, the surface of the lubricant layer of the packaging material preferably has a static friction coefficient at 60° C. of 0.75 or more.
[0019] In this case, when the battery cells of the energy storage device are placed between two exterior materials with the lubricant layer facing the battery cells and pressure is applied to the battery cells via the exterior materials, even if the energy storage device is operated and the battery cells heat up to 60°C or higher, the static friction coefficient of the exterior materials against the battery cells becomes larger, and slippage of the exterior materials against the battery cells can be more sufficiently suppressed. This makes it possible to prevent the battery cells from becoming misaligned relative to the exterior materials, particularly when the battery cells become larger and their own weight increases.
[0020] In the packaging material for an electricity storage device, it is preferable that the surface of the lubricant layer of the packaging material has a static friction coefficient at 23° C. of 0.4 or less.
[0021] In this case, since the static friction coefficient at 23°C on the surface of the lubricant layer of the packaging material is 0.4 or less, when a mold is used to form a recess in the packaging material from the side of the lubricant layer, the mold slides easily against the lubricant layer, the static friction coefficient applied to the packaging material by the mold is reduced, and the packaging material is less likely to break or crack. Therefore, the packaging material for an electricity storage device has excellent moldability.
[0022] In the packaging material for an electricity storage device, the electricity storage device may be an all-solid-state battery.
[0023] Another aspect of the present disclosure provides an electricity storage device including a battery cell and an exterior container that houses the battery cell, the exterior container being obtained using the exterior material for an electricity storage device described above. In this electricity storage device, the exterior material has excellent moldability, so that the exterior material is less likely to break or crack. This makes it possible to prevent moisture from entering the exterior container. Even if the battery cells generate heat during operation of the electricity storage device and the exterior material reaches a high temperature of 40°C or higher, the lubricant layer is incorporated into the heat-sealed resin layer, and the amount of the lubricant layer is 10 mg / m 2 Since the static friction coefficient of the exterior material against the battery cell is large, it is possible to suppress slippage of the exterior material against the battery cell.
[0024] The power storage device may be an all-solid-state battery. Effect of the Invention
[0025] According to the present disclosure, it is possible to provide an exterior material for an energy storage device, which has excellent formability and is capable of suppressing slippage against a battery cell even when the battery cell of the energy storage device is placed in an environment of 40°C or higher while being pressurized, and an energy storage device using the same. [Brief description of the drawings]
[0026] [Figure 1] 1 is a schematic cross-sectional view of an exterior material for a power storage device according to an embodiment of the present disclosure. [Diagram 2] 1 is a schematic cross-sectional view of an exterior material for a power storage device according to an embodiment of the present disclosure. [Diagram 3] 1 is a perspective view of an electricity storage device according to an embodiment of the present disclosure. [Figure 4] FIG. 2 is a plan view of a molded body used in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.
[0028] [Exterior materials for power storage devices] Fig. 1 is a cross-sectional view that shows a schematic diagram of an embodiment of an exterior material for a power storage device according to the present disclosure. As shown in Fig. 1, an exterior material (exterior material for a power storage device) 10 of this embodiment is a laminate including, in this order, a base layer 11, an outer adhesive layer 12a, a barrier layer 17 including a metal foil layer 13, an inner adhesive layer 12b, a sealant layer 16 as a heat-sealable resin layer, and a lubricant layer 18 including a lubricant.
[0029] The barrier layer 17 may further include a first anti-corrosion treatment layer 14a and a second anti-corrosion treatment layer 14b on both sides of the metal foil layer 13. The first anti-corrosion treatment layer 14a is provided on the surface of the metal foil layer 13 facing the base material layer 11, and the second anti-corrosion treatment layer 14b is provided on the surface of the metal foil layer 13 facing the sealant layer 16. Note that the barrier layer 17 may include only one of the first anti-corrosion treatment layer 14a and the second anti-corrosion treatment layer 14b, or may not include any anti-corrosion treatment layer.
[0030] The sealant layer 16 takes in the lubricant from the lubricant layer 18 when the exterior material 10 is placed in an environment of 40° C. or higher, and the amount of the lubricant layer 18 is 10 mg / m 2 It is possible to have the following:
[0031] Each layer constituting the packaging material 10 will now be described in more detail.
[0032] <Base material layer> The base layer 11 provides heat resistance in a sealing process when manufacturing the electricity storage device and plays a role in suppressing the occurrence of pinholes that may occur during molding and distribution. In particular, in the case of an exterior material for a large-scale electricity storage device, the base layer 11 can also provide scratch resistance, chemical resistance, insulation, and the like.
[0033] The base layer 11 is preferably a resin film formed of an insulating resin, such as polyester resin, polyamide resin, polyimide resin, polyamideimide resin, polyether ketone resin, polyphenylene sulfide resin, polyetherimide resin, polysulfone resin, fluororesin, phenol resin, melamine resin, urethane resin, allyl resin, silicone resin, epoxy resin, furan resin, acetyl cellulose resin, or the like can be used as the resin.
[0034] Among these resins, polyester resin and polyamide resin are preferable for the base layer 11 because of their excellent moldability. Examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyamide resin include nylon 6, nylon 6,6, a copolymer of nylon 6 and nylon 6,6, nylon 6, nylon 9T, nylon 10, polymetaxylylene adipamide (MXD6), nylon 11, and nylon 12. Of the polyester resins and polyamide resins, polyester resins are particularly preferred for the base material layer 11. Polyester resins are excellent in heat resistance, chemical resistance, and moldability. For this reason, even when sealing is performed to form an exterior container using the exterior material 10, the base material layer 11 is unlikely to melt. In addition, even when the exterior material 10 is used in a high-temperature environment (e.g., 120°C), the base material layer 11 is unlikely to yellow. Furthermore, the base material layer 11 is unlikely to dissolve even when it comes into contact with chemicals, and even when molding is performed on the exterior material 10, the base material layer 11 is unlikely to break.
[0035] The substrate layer 11 may be either a stretched or unstretched film, or a coating film. The substrate layer 11 may be a single layer or a multilayer, and in the case of a multilayer, layers made of different resins may be used in combination. When the substrate layer 11 is a film, the substrate layer 11 may be a layer obtained by co-extrusion of multiple resin layers, or a layer obtained by laminating multiple resin layers with an adhesive. When the substrate layer 11 has a coating film, the substrate layer 11 may be a layer coated with the coating film the number of times it is laminated, or a laminate obtained by combining a film and a coating film may be used.
[0036] When the base material layer 11 is a stretched film, the base material layer 11 may be a uniaxially stretched film or a biaxially stretched film, but is preferably a biaxially stretched film. In this case, since the base material layer 11 has high strength in two perpendicular directions, the base material layer 11 is unlikely to break even when the packaging material 10 is molded. In other words, the packaging material 10 has excellent moldability. Examples of the stretching method for the biaxially stretched film include a sequential biaxial stretching method, a tubular biaxial stretching method, a simultaneous biaxial stretching method, etc. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably one stretched by a tubular biaxial stretching method.
[0037] The base layer 11 may be a single layer film made of one type of resin film, or a laminated film made of two or more types of resin films.
[0038] The thickness of the substrate layer 11 is preferably 6 to 50 μm, and more preferably 10 to 30 μm. When the thickness of the substrate layer 11 is 6 μm or more, the pinhole resistance and insulating properties of the packaging material 10 tend to be improved. When the thickness of the substrate layer 11 is 50 μm or less, the total thickness of the packaging material 10 can be reduced.
[0039] The melting point of the base layer 11 is not particularly limited, but in order to suppress deformation of the base layer 11 during sealing, it is preferably higher than the melting point of the sealant layer 16. Furthermore, the melting point of the base layer 11 is more preferably higher than the melting point of the sealant layer 16 by 30° C. or more.
[0040] <Outer adhesive layer> The outer adhesive layer 12a is a layer that bonds the base material layer 11 and the barrier layer 17. Specific examples of materials constituting the outer adhesive layer 12a include polyurethane resins obtained by reacting a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol with a curing agent such as a difunctional or higher isocyanate compound (polyfunctional isocyanate compound). Among polyurethane resins, polyester urethane resins obtained by using polyester polyol and a difunctional or higher isocyanate compound are preferred because they are more likely to prevent the outer layer from peeling off in a high-temperature environment.
[0041] The various polyols described above can be used alone or in combination of two or more types depending on the functions and performance required for the exterior packaging material 10.
[0042] Depending on the performance required for the adhesive, various other additives and stabilizers may be blended with the polyurethane resin described above.
[0043] In the polyurethane-based adhesive used to form the outer adhesive layer 12a containing the above-mentioned polyurethane resin, the ratio (NCO / OH) of the number of isocyanato groups contained in the polyfunctional isocyanate compound to the number of hydroxyl groups contained in the polyol may be 2 to 60, 5 to 50, or 10 to 40. When this ratio is 2 or more, the adhesive strength between the base layer 11 and the metal foil layer 13 in a high-temperature environment (for example, 150°C) can be further improved, and the lifting of the base layer 11 from the metal foil layer 13 in a high-temperature environment can be further suppressed. When the ratio is 60 or less, it is possible to prevent unreacted hydroxyl groups from remaining in excess, and it is easy to further improve the adhesive strength between the base layer 11 and the barrier layer 17 in both room temperature and high-temperature environments. The heat resistance of the cured product of the polyurethane-based adhesive (outer adhesive layer 12a) is improved by urea or biuret generated by the reaction of a trace amount of water contained in the air or the adhesive with the polyfunctional isocyanate compound. Therefore, the more the polyfunctional isocyanate compound, the more these units there are, which leads to a tendency for Tg to be higher and for heat resistance to be improved. Among the polyfunctional isocyanate compounds, aliphatic (alicyclic) polyfunctional isocyanate compounds in particular have excellent heat resistance, and can further improve the adhesion between the base layer 11 and the barrier layer 17 in a high-temperature environment.
[0044] The thickness of the outer adhesive layer 12a is not particularly limited, but is preferably 1 to 10 μm, more preferably 3 to 7 μm, from the viewpoint of obtaining the desired adhesive strength, followability, processability, etc. If the thickness of the outer adhesive layer 12a is 1 μm or more, high adhesive strength is easily obtained, and stress relaxation of the shear force generated during thermal expansion of the base layer 11 and the metal foil layer 13 in a high-temperature environment is easily achieved. On the other hand, if the thickness of the outer adhesive layer 12a is 10 μm or less, the moldability of the packaging material 10 can be further improved, and the occurrence of outer layer lifting in a high-temperature environment is more easily suppressed.
[0045] <Barrier layer> The metal foil layer 13 included in the barrier layer 17 has a water vapor barrier property that prevents moisture from penetrating into the inside of the electricity storage device. In addition, the metal foil layer 13 may have extensibility for deep drawing. As the metal foil layer 13, for example, various metal foils such as aluminum, stainless steel, copper, etc. can be used. The metal foil layer 13 does not soften significantly at 120°C, and has a large effect of suppressing elongation in a high-temperature environment. Among them, aluminum foil is more preferable. Aluminum foil has high barrier properties, good formability and flexibility, and is lightweight. Therefore, the barrier properties of the exterior material 10 can be improved. Even if the exterior material 10 is molded, the metal foil layer 13 is less likely to break, and the deterioration of the barrier properties of the exterior material 10 can be suppressed. Furthermore, since the flexibility of the exterior material 10 is improved, even when a battery cell is housed in an exterior container formed using the exterior material 10, the exterior material 10 can follow the shape of the battery cell. Furthermore, since the exterior material 10 is lightweight, the volumetric energy density of the electricity storage device having the exterior material 10 can also be increased. Furthermore, since the aluminum foil does not need to be thinned to achieve good conformability, it is possible to prevent the remaining thickness of the metal foil layer 13 from becoming thin after deep drawing of the exterior packaging material 10.
[0046] As the aluminum foil, a soft aluminum foil that has been annealed can be preferably used from the viewpoint of imparting desired ductility during molding, but it is more preferable to use an aluminum foil containing iron for the purpose of imparting further pinhole resistance and ductility during molding. The content of iron in the aluminum foil is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%, in 100 mass% of the aluminum foil. When the iron content is 0.1 mass% or more, an exterior material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0 mass% or less, an exterior material 10 having better flexibility can be obtained. As the aluminum foil, an untreated aluminum foil may be used, but it is preferable to use an aluminum foil that has been degreased in terms of imparting corrosion resistance. When the aluminum foil is degreased, the degreased treatment may be performed on only one side of the aluminum foil, or on both sides.
[0047] The thickness of the metal foil layer 13 is not particularly limited, but in consideration of the barrier properties, pinhole resistance, and processability, it is preferably 9 to 200 μm, and more preferably 15 to 100 μm.
[0048] <First corrosion prevention treatment layer and second corrosion prevention treatment layer> The first corrosion prevention treatment layer 14a and the second corrosion prevention treatment layer 14b are layers provided to prevent corrosion of the metal foil (metal foil layer) constituting the metal foil layer 13. The first corrosion prevention treatment layer 14a plays a role of increasing the adhesion between the metal foil layer 13 and the outer adhesive layer 12a. The second corrosion prevention treatment layer 14b plays a role of increasing the adhesion between the metal foil layer 13 and the inner adhesive layer 12b. The first corrosion prevention treatment layer 14a and the second corrosion prevention treatment layer 14b may be layers of the same configuration or layers of different configurations. The first and second corrosion prevention treatment layers 14a, 14b (hereinafter also simply referred to as "corrosion prevention treatment layers 14a, 14b") are formed, for example, by degreasing treatment, hydrothermal conversion treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments.
[0049] Examples of the degreasing treatment include acid degreasing and alkaline degreasing. Examples of the acid degreasing include a method using an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or hydrofluoric acid alone or a mixture thereof. In addition, by using an acid degreasing agent in which a fluorine-containing compound such as monosodium ammonium difluoride is dissolved in the inorganic acid as the acid degreasing, not only can the aluminum be degreased, but also a fluoride of aluminum, which is passive, can be formed, particularly when an aluminum foil is used for the metal foil layer 13. Therefore, using an acid degreasing agent in which a fluorine-containing compound such as monosodium ammonium difluoride is dissolved in the inorganic acid as the acid degreasing is effective in terms of corrosion resistance. Examples of the alkaline degreasing include a method using sodium hydroxide or the like.
[0050] An example of the hydrothermal modification treatment is a boehmite treatment in which an aluminum foil is immersed in boiling water containing added triethanolamine.
[0051] An example of the anodizing treatment is an alumite treatment.
[0052] The chemical conversion treatment may be of the immersion type or the coating type. Examples of the immersion type chemical conversion treatment include chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or various chemical conversion treatments consisting of a mixture of these. On the other hand, examples of the coating type chemical conversion treatment include a method in which a coating agent having corrosion prevention properties is applied onto the metal foil layer 13.
[0053] When forming at least a part of the corrosion prevention layer by any of these corrosion prevention treatments, namely, hydrothermal conversion treatment, anodizing treatment, and chemical conversion treatment, it is preferable to perform the above-mentioned degreasing treatment in advance. When using a degreased metal foil, such as a metal foil that has been subjected to an annealing process, as the metal foil layer 13, there is no need to perform a degreasing treatment again in forming the corrosion prevention layers 14a and 14b.
[0054] The coating agent used in the spray-type chemical conversion treatment preferably contains trivalent chromium. The coating agent may also contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers, which will be described later.
[0055] Among the above treatments, particularly in hydrothermal conversion treatment and anodization treatment, the aluminum foil surface is dissolved by a treatment agent to form an aluminum compound (boehmite, alumite) having excellent corrosion resistance. Therefore, the metal foil layer 13 using the aluminum foil to the corrosion prevention treatment layers 14a, 14b form a bicontinuous structure, so the above treatment is included in the definition of chemical conversion treatment. On the other hand, as described later, it is also possible to form the corrosion prevention treatment layers 14a, 14b by a pure coating method that is not included in the definition of chemical conversion treatment. As an example of this method, a method using a sol of a rare earth element oxide such as cerium oxide with an average particle size of 100 nm or less can be mentioned as a material that has an aluminum corrosion prevention effect (inhibitor effect) and is also environmentally friendly. By using this method, it is possible to impart a corrosion prevention effect to a metal foil such as an aluminum foil even by a general coating method.
[0056] Examples of the rare earth element oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, ether-based, etc. Among these, water-based sols are preferred.
[0057] In order to stabilize the dispersion of the rare earth oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, etc. or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, lactic acid, etc. are usually used as dispersion stabilizers. Among these dispersion stabilizers, phosphoric acid in particular is expected to (1) stabilize the dispersion of the sol, (2) improve adhesion to the metal foil layer 13 by utilizing the aluminum chelating ability of phosphoric acid, and (3) improve the cohesive force of the corrosion prevention treatment layers 14a, 14b (oxide layers) by easily causing dehydration condensation of phosphoric acid even at low temperatures.
[0058] The corrosion prevention layers 14a and 14b formed from the rare earth oxide sol are aggregates of inorganic particles, and therefore may lose their cohesive strength even after the drying and curing process. Therefore, it is preferable that the corrosion prevention layers 14a and 14b in this case are compounded with an anionic polymer or a cationic polymer to compensate for the cohesive strength.
[0059] The corrosion prevention treatment layers 14a and 14b are not limited to the above-mentioned layers. For example, they may be formed using a treatment agent in which phosphoric acid and a chromium compound are mixed with a resin binder (such as aminophenol), as in the case of coating-type chromate, which is a known technology. By using this treatment agent, a layer having both corrosion prevention function and adhesion can be obtained. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent in which a rare earth oxide sol and a polycationic polymer or a polyanionic polymer are mixed in advance into a one-component solution can be used to obtain a layer having both corrosion prevention function and adhesion.
[0060] The mass per unit area of the corrosion prevention layers 14a and 14b is 0.005 to 0.200 g / m2 regardless of whether the layer has a multi-layer structure or a single-layer structure. 2 is preferable, and 0.010 to 0.100 g / m 2 It is more preferable that the mass per unit area is 0.005 g / m 2 If the mass per unit area is 0.200 g / m or more, it is easy to impart a corrosion prevention function to the metal foil layer 13. 2 Even if the thickness exceeds 100 mm, the corrosion prevention function does not change much. On the other hand, when a rare earth oxide sol is used, if the coating is thick, the heat curing during drying may be insufficient, which may result in a decrease in cohesive force. The thickness of the corrosion prevention layers 14a and 14b can be calculated from their specific gravity.
[0061] From the viewpoint of easily maintaining the adhesion between the sealant layer 16 and the metal foil layer 13, the corrosion prevention treatment layers 14a, 14b may be in an embodiment containing, for example, cerium oxide, 1 to 100 parts by mass of phosphoric acid or a phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer, or may be formed by subjecting the metal foil layer 13 to a chemical conversion treatment, or may be formed by subjecting the metal foil layer 13 to a chemical conversion treatment and contain a cationic polymer.
[0062] <Inner adhesive layer> The inner adhesive layer 12b is a layer that bonds the metal foil layer 13, on which the second corrosion prevention treatment layer 14b is formed, to the sealant layer 16. For the inner adhesive layer 12b, a general adhesive for bonding a metal foil layer and a sealant layer can be used, and for example, the same adhesive as that for the outer adhesive layer 12a described above can be used.
[0063] The thickness of the inner adhesive layer 12b is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, processability, and the like, it is preferably 1 to 10 μm, and more preferably 3 to 7 μm.
[0064] <Sealant layer> The sealant layer 16 is a layer that provides the packaging material 10 with sealability by heat sealing. The sealant layer 16 may be a resin film containing a base resin. Examples of the base resin include polyolefin-based resins and polyester-based resins. These may be used alone or in combination of two or more. Polyolefin-based resins and polyester-based resins are not only excellent in heat sealability but also have a certain degree of flexibility, so that when the sealant layer 16 contains at least one of a polyolefin-based resin and a polyester-based resin, the exterior material 10 is less likely to curl even if the sealant layer 16 is thicker than the base layer 11. It is particularly preferable that the sealant layer 16 contains a polyolefin resin. In this case, not only is the heat sealability of the sealant layer 16 improved, but the moisture permeability is also likely to be reduced, allowing the packaging material 10 to have high heat sealability and barrier properties.
[0065] Examples of polyolefin resins include low-, medium- or high-density polyethylene, ethylene-α-olefin copolymer, homopolypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer. Among them, the polyolefin resin is preferably composed of at least one of homopolypropylene and block polypropylene. Compared to random polypropylene, homopolypropylene and block polypropylene are excellent not only in heat resistance but also in hardness. Therefore, when the sealant layer 16 is composed of at least one of homopolypropylene and block polypropylene, the base layer 11 can be made thicker and harder. As a result, the exterior material 10 can have excellent moldability and can also be prevented from curling.
[0066] Examples of polyester-based resins include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and copolymers thereof.
[0067] The sealant layer 16 may contain a polyolefin-based elastomer. The polyolefin-based elastomer may be compatible with the above-mentioned base resin or may not be compatible with it, and may contain both a compatible polyolefin-based elastomer that is compatible and a non-compatible polyolefin-based elastomer that is not compatible with it. Being compatible (compatible system) means that the elastomer disperses in the base resin with a dispersed phase size of 1 nm or more and less than 500 nm. Not being compatible (non-compatible system) means that the elastomer disperses in the base resin with a dispersed phase size of 500 nm or more and less than 20 μm.
[0068] When the base resin is a polypropylene resin, the compatible polyolefin elastomer may be, for example, a propylene-butene-1 random copolymer, and the incompatible polyolefin elastomer may be, for example, an ethylene-butene-1 random copolymer. The polyolefin elastomers may be used alone or in combination of two or more.
[0069] The sealant layer 16 may also contain additives such as slip agents, antioxidants, light stabilizers, and flame retardants. The content of these additives is preferably 5 parts by mass or less, assuming that the total mass of the sealant layer 16 is 100 parts by mass. The sealant layer 16 may also contain a lubricant as an additive. The lubricant is not particularly limited, but preferably includes amide-based lubricants, silicone oil, etc. Specific examples of amide-based lubricants include fatty acid amides such as saturated fatty acid amides and unsaturated fatty acid amides; and fatty acid bisamides such as saturated fatty acid bisamides and unsaturated fatty acid bisamides. Among them, fatty acid amides are preferred from the viewpoint of film-forming properties of the sealant layer 16. Specific examples of saturated fatty acid amides include lauric acid amide, palmitic acid amide, stearic acid amide, etc. Specific examples of unsaturated fatty acid amides include oleic acid amide, erucic acid amide, etc. Specific examples of the saturated fatty acid bisamide include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, etc. Specific examples of the unsaturated fatty acid bisamide include ethylene biserucic acid amide, ethylene bisoleic acid amide, etc. The boiling point of the lubricant is not particularly limited, but is preferably 180° C. or higher. In this case, volatilization of the lubricant is suppressed even if the exterior material 10 is placed in a high-temperature environment of 150° C. or higher. Examples of such lubricants include the above-mentioned fatty acid amides and fatty acid bisamides. The lubricant may be used alone or in combination of two or more kinds. The content of the lubricant in the sealant layer 16 is set so that when the exterior material 10 is placed in an environment of 40° C. or higher, the sealant layer 16 takes in the lubricant from the lubricant layer 18 and the amount of the lubricant layer 18 is 10 mg / m 2 There are no particular limitations on the amount as long as it is possible to achieve the following, but the lower the lubricant content in the sealant layer 16, the easier it is for the sealant layer 16 to absorb the lubricant from the lubricant layer 18 when the exterior material 10 is placed in an environment of 40° C. or higher. The amount of lubricant layer 18 when the exterior material 10 is placed in an environment of 40° C. or higher refers to the amount of lubricant layer 18 when the exterior material 10 is placed in an environment of 40° C. or higher for two weeks (336 hours). The content of the lubricant in the sealant layer 16 may be 1000 ppm by mass or less, 500 ppm by mass or less, or less than 200 ppm by mass, but is preferably less than 200 ppm by mass. In this case, when the exterior material 10 is placed in an environment of 40° C. or more, the sealant layer 16 can effectively take in the lubricant from the lubricant layer 18. For this reason, for example, after placing the exterior material 10 in an environment of 40° C. or more, a battery cell of an electricity storage device is placed between two exterior materials 10 with the lubricant layer 18 facing the battery cell side, and the battery cell is pressurized via the exterior material 10, the static friction coefficient of the exterior material 10 against the battery cell becomes larger, and the slippage of the exterior material 10 against the battery cell can be more sufficiently suppressed. The content of the lubricant in the sealant layer 16 is preferably 150 ppm by mass or less, more preferably 120 ppm by mass or less, further preferably 100 ppm by mass or less, and particularly preferably 50 ppm by mass or less. The content of the lubricant in the sealant layer 16 may be 0 ppm by mass, but from the viewpoint of processability, it is preferably 10 ppm by mass or more, more preferably 20 ppm by mass or more, and particularly preferably 50 ppm by mass or more. The surface roughness Sa of the surface of the sealant layer 16 on the side of the lubricant layer 18 is not particularly limited and may be preferably less than 1.5 μm or 1.0 μm or less, but is preferably 1.0 μm or less. The surface roughness Sa of the surface of the sealant layer 16 on the side of the lubricant layer 18 also affects the slipperiness of the mold. If the surface roughness Sa of the surface of the sealant layer 16 on the side of the lubricant layer 18 is 1.0 μm or less, the contact area between the exterior material 10 and the battery cell can be increased after the lubricant contained in the lubricant layer 18 is taken up into the sealant layer 16, making it possible to make the exterior material 10 less slippery relative to the battery cell. The surface roughness Sa of the surface of the sealant layer 16 on the side of the lubricant layer 18 is preferably less than 0.7 μm, more preferably 0.50 μm or less, and particularly preferably 0.30 μm or less. From the viewpoint of moldability, the surface roughness Sa of the surface of the sealant layer 16 on the side of the lubricant layer 18 is preferably 0.12 μm or more, and more preferably 0.15 μm or more.
[0070] The sealant layer 16 may be either a single layer film or a multilayer film, and may be selected according to the required function. When the sealant layer 16 is a multilayer film, the layers may be laminated together by coextrusion or by dry lamination.
[0071] The thickness of the sealant layer 16 is not particularly limited, but from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment, it is preferably in the range of 5 to 100 μm, more preferably in the range of 10 to 100 μm, and even more preferably in the range of 20 to 80 μm.
[0072] <Lubricant layer> The lubricant layer 18 contains a lubricant. The lubricant is not particularly limited, but preferably includes amide-based lubricants and silicone oil.Specific examples of amide-based lubricants include fatty acid amides such as saturated fatty acid amides and unsaturated fatty acid amides; fatty acid bisamides such as saturated fatty acid bisamides and unsaturated fatty acid bisamides.Among them, fatty acid amides are preferred from the viewpoint of processability.
[0073] Specific examples of saturated fatty acid amides include lauric acid amide, palmitic acid amide, stearic acid amide, etc. Specific examples of unsaturated fatty acid amides include oleic acid amide, erucic acid amide, etc. Specific examples of the saturated fatty acid bisamide include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, etc. Specific examples of the unsaturated fatty acid bisamide include ethylene biserucic acid amide, ethylene bisoleic acid amide, etc. The lubricant may be used alone or in combination of two or more kinds.
[0074] The boiling point of the lubricant is not particularly limited, but is preferably 180° C. or higher. In this case, volatilization of the lubricant is suppressed even if the exterior material 10 is placed in a high-temperature environment of 150° C. or higher. Examples of such lubricants include the above-mentioned fatty acid amides and fatty acid bisamides.
[0075] The lubricant may be the same as or different from the lubricant contained in the sealant layer 16, but it is preferable that they are the same. The behavior of the lubricant in the lubricant layer 18 being taken up into the sealant layer 16 or conversely bleeding out from the sealant layer 16 differs depending on the type of lubricant in the sealant layer 16, but when the lubricant in the lubricant layer 18 is the same as the lubricant contained in the sealant layer 16, that behavior can be easily controlled.
[0076] The amount of the lubricant layer 18 is 10 mg / m 2 Even if it is less than 10 mg / m 2 More is acceptable, but not more than 10 mg / m2 It is preferable that the amount of the lubricant layer 18 is more than 10 mg / m 2 With a larger amount of lubricant layer 18, when a recess is formed in exterior material 10 from the side of lubricant layer 18 using a mold, the mold slides easily against lubricant layer 18, the static friction coefficient that the mold exerts on exterior material 10 is reduced, and breaks and cracks are less likely to occur in exterior material 10. The amount of lubricant layer 18 is set so that when exterior material 10 is placed in an environment of 40° C. or higher, the amount of lubricant layer 18 is 10 mg / m 2 The amount is adjusted as follows: The amount of the lubricant layer 18 is preferably 15 mg / m from the viewpoint of moldability. 2 More preferably, it is 20 mg / m 2 More preferably, it is 25 mg / m 2 That's all. The amount of the lubricant layer 18 is preferably 40 mg / m from the viewpoint of preventing slippage of the battery cell after molding. 2 More preferably, it is 30 mg / m or less. 2 The following is the result.
[0077] The lubricant layer 18 is preferably obtained by coating a composition containing a lubricant. Since the lubricant layer 18 is obtained by coating a composition containing a lubricant, the amount of the lubricant layer 18 is easy to control. For this reason, the amount of the lubricant layer 18 is set to 10 mg / m2, which exhibits excellent moldability. 2 Since the amount of the lubricant layer 18 can be adjusted to a larger amount, the moldability is stabilized. In addition, since the lubricant layer 18 is obtained by coating a composition containing a lubricant, the amount of the lubricant layer 18 can be set to be equal to or less than the amount of the lubricant that can be incorporated in the sealant layer 16.
[0078] The static friction coefficient at 60° C. on the surface of the lubricant layer 18 of the exterior material 10 is not particularly limited, but is preferably 0.75 or more. In this case, when the battery cells of the electricity storage device are placed between the two exterior materials 10 with the lubricant layer 18 facing the battery cell side and the battery cells are pressurized via the exterior material 10, when the electricity storage device is operated and the battery cells heat up to 60°C or higher, the static friction coefficient of the exterior material 10 against the battery cells becomes larger, making it possible to more sufficiently suppress the sliding of the exterior material 10 against the battery cells. Therefore, it is possible to make it less likely for the battery cells to become misaligned with respect to the exterior material 10, particularly when the battery cells become larger and their mass increases. The static friction coefficient at 60° C. is more preferably 0.80 or more, and particularly preferably 0.85 or more. The static friction coefficient at 60° C. may be 1.3 or less. The static friction coefficient is measured by the tilt method in accordance with JIS P8147. Specifically, a friction coefficient measuring device (product name "AN-S2", manufactured by Toyo Seiki Co., Ltd.) is used, a laminate of exterior material 10 and a thread (dimensions: 60 mm x 100 mm, mass: 1000 g) is placed on an inclined plate with exterior material 10 facing the inclined plate side, the inclined plate is tilted at a speed of 1.5° / s, and the static friction coefficient is calculated from the maximum static friction force and normal force when exterior material 10 starts to slide.
[0079] The static friction coefficient at 23° C. on the surface of lubricant layer 18 of packaging material 10 is not particularly limited, but is preferably 0.4 or less. In this case, if the static friction coefficient at 23° C. on the surface of lubricant layer 18 of packaging material 10 is 0.4 or less, when a mold is used to form a recess in packaging material 10 from the side of lubricant layer 18, the mold slides easily against lubricant layer 18, the static friction coefficient that the mold imparts to packaging material 10 is reduced, and breakage or cracks are less likely to occur in packaging material 10. Therefore, packaging material 10 has excellent moldability. The static friction coefficient at 23° C. is more preferably 0.2 or less, and particularly preferably 0.15 or less. The static friction coefficient at 23° C. is preferably 0.08 or more, and more preferably 0.09 or more. When the static friction coefficient at 23° C. is 0.08 or more, the handleability of the exterior material 10 during the production of the electricity storage device is improved. That is, when the exterior material 10 is transported by hand or machine before and after molding of the exterior material 10, the exterior material 10 becomes less slippery and easier to handle.
[0080] Although a preferred embodiment of the exterior material for a power storage device according to the present embodiment has been described in detail above, the present disclosure is not limited to such a specific embodiment, and various modifications and variations are possible within the scope of the gist of the present disclosure as described in the claims.
[0081] For example, in FIG. 1, the exterior material 10 includes the outer adhesive layer 12a and the inner adhesive layer 12b, but at least one of these may be omitted.
[0082] 1 shows a case where the barrier layer 17 and the sealant layer 16 are laminated using the inner adhesive layer 12b, but the barrier layer 17 and the sealant layer 16 may be laminated using an adhesive resin layer 15 as in the electrical storage device packaging material 20 shown in FIG 2. In this case, the laminate of the adhesive resin layer 15 and the sealant layer 16 constitutes a heat-sealed resin layer. In addition, in the electrical storage device packaging material 20 shown in FIG 2, an inner adhesive layer 12b may be further provided between the barrier layer 17 and the adhesive resin layer 15.
[0083] <Adhesive resin layer> The adhesive resin layer 15 is generally composed of an adhesive resin composition as a main component and additives as necessary. The adhesive resin composition is not particularly limited, but preferably contains a modified polyolefin resin.
[0084] The modified polyolefin resin is preferably a polyolefin resin graft-modified with an unsaturated carboxylic acid derivative derived from an unsaturated carboxylic acid, an acid anhydride, or an ester thereof.
[0085] Examples of polyolefin resins include low density polyethylene, medium density polyethylene, high density polyethylene, ethylene-α-olefin copolymer, homopolypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.
[0086] The modified polyolefin resin is preferably a polyolefin resin modified with maleic anhydride. For example, "Admer" manufactured by Mitsui Chemicals, Inc. and "Modic" manufactured by Mitsubishi Chemical Corporation are suitable for the modified polyolefin resin. Since such modified polyolefin resins have excellent reactivity with various metals and polymers having various functional groups, the adhesive resin layer 15 can be given adhesion by utilizing the reactivity. In addition, the adhesive resin layer 15 may contain various additives such as various compatible and incompatible elastomers, flame retardants, slip agents, antiblocking agents, antioxidants, light stabilizers, and tackifiers, as necessary.
[0087] The thickness of the adhesive resin layer 15 is not particularly limited, but from the viewpoints of stress relaxation and moisture permeability, it is preferably the same as or less than that of the sealant layer 16 .
[0088] In addition, in the exterior packaging material 20 for a storage battery device, the total thickness of the adhesive resin layer 15 and the sealant layer 16 is preferably in the range of 5 to 100 μm, and more preferably in the range of 20 to 80 μm, from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment.
[0089] [Exterior material manufacturing method] Next, there will be described an example of a method for manufacturing the exterior packaging material 10 shown in Fig. 1. Note that the method for manufacturing the exterior packaging material 10 is not limited to the following method.
[0090] The manufacturing method of the exterior material 10 of the present embodiment is roughly composed of the steps of providing corrosion prevention treatment layers 14a, 14b on the metal foil layer 13 to form a barrier layer 17, bonding the base material layer 11 and the barrier layer 17 together using the outer adhesive layer 12a, further laminating the sealant layer 16 via the inner adhesive layer 12b to produce a laminate, and, if necessary, aging the obtained laminate, and forming a lubricant layer 18 on the sealant layer 16 of the laminate.
[0091] (Barrier layer formation process) This step is a step of forming the corrosion prevention treatment layers 14a, 14b on the metal foil layer 13 to form the barrier layer 17. As described above, examples of the method include subjecting the metal foil layer 13 to a degreasing treatment, a hydrothermal conversion treatment, an anodizing treatment, or a chemical conversion treatment, or applying a coating agent having corrosion prevention properties.
[0092] Furthermore, when the corrosion prevention treatment layers 14a, 14b are multi-layered, for example, a coating liquid (coating agent) constituting the lower corrosion prevention treatment layer (metal foil layer 13 side) may be applied to the metal foil layer 13 and baked to form a first layer, and then a coating liquid (coating agent) constituting the upper corrosion prevention treatment layer may be applied to the first layer and baked to form a second layer.
[0093] The degreasing treatment may be performed by spraying or immersion. The hydrothermal conversion treatment and anodizing treatment may be performed by immersion. The chemical conversion treatment may be performed by an appropriate method such as immersion, spraying, or coating, depending on the type of chemical conversion treatment.
[0094] Regarding the coating method of the coating agent having corrosion prevention properties, various methods such as gravure coating, reverse coating, roll coating, bar coating, etc. can be used.
[0095] As described above, the various treatments may be performed on either one or both sides of the metal foil, but in the case of one-sided treatment, it is preferable to perform the treatment only on the side on which the sealant layer 16 is laminated. If required, the above treatments may also be performed on the surface of the base layer 11.
[0096] The amount of coating agent applied to form the first layer and the second layer is 0.005 to 0.200 g / m 2 is preferable, and 0.010 to 0.100 g / m 2 is more preferred.
[0097] Furthermore, when dry curing is required, the dry curing can be performed at a base material temperature in the range of 60 to 300° C. depending on the drying conditions of the corrosion prevention treatment layers 14a and 14b used.
[0098] (Laminating process of substrate layer and barrier layer) This step is a step of bonding the barrier layer 17 and the base material layer 11 via the outer adhesive layer 12a. The bonding method may be dry lamination, non-solvent lamination, wet lamination, or the like, and the two are bonded together using the material constituting the outer adhesive layer 12a described above. The outer adhesive layer 12a has a dry coating amount of 1 to 10 g / m 2 More preferably, the range is 2 to 7 g / m 2 It is set within the range.
[0099] Specific examples of materials constituting the outer adhesive layer 12a include polyurethane resins obtained by reacting a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol with a bifunctional or higher isocyanate compound (polyfunctional isocyanate compound). In this case, it is preferable to use an aliphatic isocyanate compound as the polyfunctional isocyanate compound, and it is more preferable to use an alicyclic isocyanate compound. In this case, the heat resistance of the outer adhesive layer 12a is further improved, so that the base layer 11 and the barrier layer 17 can maintain their adhesion even at a high temperature of 120°C.
[0100] (Lamination process of inner adhesive layer and sealant layer) This step is a step of bonding the sealant layer 16 via the inner adhesive layer 12b to the second corrosion prevention treatment layer 14b side of the barrier layer 17. Examples of the bonding method include a wet process and dry lamination.
[0101] In the case of the wet process, a solution or dispersion of the adhesive constituting the inner adhesive layer 12b is applied onto the second corrosion prevention treatment layer 14b, and the solvent is removed at a predetermined temperature to form a dry film, or a baking process is performed as necessary after the dry film is formed. Then, a sealant layer 16 as a thermally adhesive resin layer is laminated to produce the exterior material 10. Examples of the coating method include the various coating methods exemplified above. The preferred dry coating amount of the inner adhesive layer 12b is the same as that of the outer adhesive layer 12a.
[0102] In this case, the sealant layer 16 can be produced, for example, by a melt extrusion molding machine using a resin composition for forming a sealant layer that contains the above-mentioned components of the sealant layer 16. In the melt extrusion molding machine, the processing speed can be set to 80 m / min or more from the viewpoint of productivity. At this time, when the exterior packaging material 10 is placed in an environment of 40° C. or higher, the sealant layer 16 takes in the lubricant from the lubricant layer 18, and the amount of the lubricant layer 18 is 10 mg / m 2 It is formed so as to enable the following:
[0103] (Aging process) This step is a step of aging (curing) the laminate. By aging the laminate, it is possible to promote adhesion between the metal foil layer 13, the second corrosion prevention treatment layer 14b, the inner adhesive layer 12b, and the sealant layer 16. The aging treatment can be carried out at a temperature in the range of room temperature to 100°C. The aging time is, for example, 1 to 10 days.
[0104] (Lubricant layer formation process) This step is a step for forming the lubricant layer 18. The lubricant layer 18 can be formed by preparing a composition containing a lubricant and applying this composition to the surface of the sealant layer 16 . When the exterior material 10 is placed in an environment of 40° C. or higher, the lubricant is absorbed from the lubricant layer 18, and the amount of the lubricant layer 18 is increased to 10 mg / m 2 The amount is adjusted so that the following can be achieved:
[0105] In this manner, the exterior packaging material 10 of the present embodiment as shown in FIG. 1 can be manufactured.
[0106] Next, a description will be given of an example of a method for manufacturing the exterior material 20 shown in Fig. 2. Note that the method for manufacturing the exterior material 20 is not limited to the following method.
[0107] The manufacturing method of the packaging material 20 of this embodiment is generally composed of a step of providing corrosion prevention treatment layers 14a, 14b on the metal foil layer 13 to form the barrier layer 17, a step of bonding the base material layer 11 and the barrier layer 17 using the outer layer adhesive layer 12a, a step of further laminating a heat-sealable resin layer consisting of an adhesive resin layer 15 and a sealant layer 16 to prepare a laminate, and a step of heat-treating the obtained laminate as necessary, and a step of forming a lubricant layer 18 on the sealant layer 16. Note that the steps up to the step of bonding the base material layer 11 and the barrier layer 17 and the step of forming the lubricant layer 18 on the sealant layer 16 can be performed in the same manner as in the manufacturing method of the packaging material 10 described above.
[0108] (Laminating process of adhesive resin layer and sealant layer) This step is a step of forming an adhesive resin layer 15 and a sealant layer 16 on the second corrosion prevention treatment layer 14b formed in the previous step. The method includes a method of sand laminating the adhesive resin layer 15 together with the sealant layer 16 using an extrusion laminator. Furthermore, the adhesive resin layer 15 and the sealant layer 16 can also be laminated by a tandem lamination method or a co-extrusion method in which the adhesive resin layer 15 and the sealant layer 16 are extruded. In forming the adhesive resin layer 15 and the sealant layer 16, for example, each component is blended so as to satisfy the above-mentioned configuration of the adhesive resin layer 15 and the sealant layer 16. The above-mentioned resin composition for forming the sealant layer is used to form the sealant layer 16.
[0109] This process produces a laminate in which the layers are stacked in the following order: base layer 11 / outer adhesive layer 12a / first corrosion prevention treatment layer 14a / metal foil layer 13 / second corrosion prevention treatment layer 14b / thermal fusion resin layer (adhesive resin layer 15 / sealant layer 16), as shown in FIG. 2.
[0110] The adhesive resin layer 15 may be laminated by directly extruding the materials dry-blended to have the above-mentioned material composition using an extrusion laminator. Alternatively, the adhesive resin layer 15 may be laminated by extruding the granulated material, which has been previously melt-blended using a melt kneading device such as a single-screw extruder, a twin-screw extruder, or a Brabender mixer, using an extrusion laminator.
[0111] The sealant layer 16 may be laminated by directly extruding the materials dry-blended to the above-mentioned material composition as the constituents of the resin composition for forming the sealant layer using an extrusion laminator. Alternatively, the adhesive resin layer 15 and the sealant layer 16 may be laminated by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded using an extrusion laminator, or a co-extrusion method, using a granulated product obtained by melt blending in advance using a melt kneading device such as a single screw extruder, a twin screw extruder, or a Brabender mixer. The adhesive resin layer 15 and the sealant layer 16 may also be laminated by a method in which a sealant monolayer is formed in advance as a cast film using the resin composition for forming the sealant layer, and this film is sandwich-laminated together with the adhesive resin. The forming speed (processing speed) of the adhesive resin layer 15 and the sealant layer 16 may be, for example, 80 m / min or more from the viewpoint of productivity.
[0112] (Heat treatment process) This step is a step of heat-treating the laminate. Heat-treating the laminate can improve adhesion between the metal foil layer 13, the second corrosion prevention treatment layer 14b, the adhesive resin layer 15, and the sealant layer 16. As a method of heat treatment, a method of treating at a temperature at least equal to or higher than the melting point of the adhesive resin layer 15 is preferable.
[0113] In this manner, the exterior packaging material 20 of this embodiment as shown in FIG. 2 can be manufactured.
[0114] [Electricity storage device] Next, an embodiment of a power storage device according to another aspect of the present disclosure will be described with reference to FIG. FIG. 3 is a perspective view showing an embodiment of a power storage device produced using the above-mentioned exterior material. As shown in FIG. 3, the power storage device 50 includes a battery cell 52 and an exterior container 54 that houses the battery cell 52. The exterior container 54 is obtained using the above-mentioned exterior material 10. In the exterior material 10, the base material layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. The exterior container 54 is configured to contain the battery cell 52 inside by folding one laminate film in half and heat-sealing it, or by overlapping two laminate films and heat-sealing them, so that the base material layer 11 is on the outer side of the power storage device 50 and the sealant layer 16 is on the inner side of the power storage device 50. The power storage device 50 may further include two metal terminals (current extraction terminals) 53 for extracting current from the battery cell 52 to the outside. In the power storage device 50, the exterior container 54 may be formed using the exterior material 20 instead of the exterior material 10.
[0115] The battery cell 52 has an electrolyte interposed between a positive electrode and a negative electrode. The metal terminal 53 is a part of the current collector taken out from the exterior material 10, and is made of a metal foil such as copper foil or aluminum foil. Examples of the negative electrode include a silicon-based negative electrode and a carbon-based negative electrode. The power storage device of the present disclosure is particularly effective when the negative electrode is a silicon-based negative electrode. This is because the silicon-based negative electrode is said to increase in volume by 300 to 400% when it absorbs Li during charging, and the exterior material of the present disclosure is useful.
[0116] According to the electricity storage device 50 of this embodiment, the exterior material 10 has excellent moldability, so that the exterior material 10 is less likely to break or crack. This makes it possible to suppress the intrusion of moisture into the exterior container 54. Furthermore, even if the battery cells 52 generate heat during operation of the electricity storage device 50 and the exterior material 10 reaches a high temperature of 40° C. or more, the lubricant layer 18 is incorporated into the sealant layer 16, and the amount of the lubricant layer 18 is 10 mg / m 2 Since the static friction coefficient of the exterior material 10 against the battery cells 52 is large, slippage of the exterior material 10 against the battery cells 52 can be suppressed.
[0117] The power storage device 50 of this embodiment may be an all-solid-state battery. When the power storage device 50 is an all-solid-state battery, the power storage device 50 is used in a state in which the battery cells 52 are pressurized via the exterior material 10 of the exterior container 54 in order to improve the performance of the power storage device 50. Here, in order to maintain the performance of the power storage device 50, it is desirable to suppress slippage between the battery cells 52 and the exterior material 10 even when the power storage device 50 is subjected to vibration. In this regard, the power storage device 50 can suppress slippage of the exterior material 10 relative to the battery cells 52 even when the power storage device 50 is subjected to vibration, and therefore the power storage device 50 is particularly useful when it is an all-solid-state battery. The electrolyte of the battery cell 52 is a solid electrolyte such as a sulfide-based solid electrolyte.
[0118] The power storage device of the present disclosure may be, for example, a power storage device such as a secondary battery, such as a lithium ion battery, a nickel metal hydride battery, or a lead acid battery, or an electrochemical capacitor, such as an electric double layer capacitor.
[0119] The outline of this disclosure is as follows. [1] An electrical storage device packaging material including a base layer, a barrier layer including a metal foil layer, and a heat-sealable resin layer in this order, the electrical storage device packaging material including a lubricant layer including a lubricant being provided on the surface of the heat-sealable resin layer, the heat-sealable resin layer taking in the lubricant from the lubricant layer when the electrical storage device packaging material is placed in an environment of 40°C or higher, and the amount of the lubricant layer being 10 mg / m 2 The exterior material for an electricity storage device can be as follows: [2] The packaging material for a storage battery device according to [1], wherein the heat-sealable resin layer includes a sealant layer, and the sealant layer has a lubricant content of less than 200 ppm by mass. [3] The packaging material for a storage battery device according to [1] or [2], wherein the heat-sealable resin layer includes a sealant layer, and the sealant layer includes a polyolefin resin. [4] The exterior packaging material for a power storage device according to any one of [1] to [3], wherein the lubricant contained in the lubricant layer is a fatty acid amide. [5] The exterior packaging material for a power storage device according to any one of [1] to [4], wherein the lubricant layer is obtained by coating a composition containing the lubricant. [6] The packaging material for a power storage device according to any one of [1] to [5], wherein the surface roughness Sa of the surface of the heat-sealable resin layer on the side of the lubricant layer is 1.0 μm or less. [7] The packaging material for a power storage device according to any one of [1] to [6], further comprising an adhesive layer between the base layer and the barrier layer. [8] The exterior material for a power storage device according to any one of [1] to [7], wherein the surface of the lubricant layer of the exterior material has a static friction coefficient of 0.75 or more at 60°C. [9] The exterior material for a power storage device according to any one of [1] to [8], wherein the surface of the lubricant layer of the exterior material has a static friction coefficient of 0.4 or less at 23°C.
[10] The exterior packaging material for an electricity storage device according to any one of [1] to [9], wherein the electricity storage device is an all-solid-state battery.
[11] An electricity storage device comprising: a battery cell; and an outer container that houses the battery cell, the outer container being obtained using the outer casing material for an electricity storage device according to any one of [1] to
[10] .
[12] The power storage device according to
[11] , which is an all-solid-state battery. EXAMPLES
[0120] The present disclosure will be described more specifically below with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.
[0121] [Materials used] The materials used in the examples and comparative examples are shown below.
[0122] <Base material layer> The base layer is made of easily moldable PET (manufactured by Unitika Ltd., thickness: 25 μm).
[0123] <Resin composition for forming first adhesive layer> The resin composition for forming the first adhesive layer was a polyester urethane adhesive made by mixing a polyester polyol (manufactured by Toyo Morton, product name: TMK-55) as the main agent and a TDI or IPDI-based isocyanate (manufactured by Toyo Morton, product name: CAT-RT1) as the curing agent and diluting with a solvent.
[0124] <Barrier layer> The barrier layer used was a layer formed by forming a first anti-corrosion treatment layer and a second anti-corrosion treatment layer on both sides of a metal foil layer.
[0125] (metal foil layer) As the metal foil layer, a soft aluminum foil that had been annealed and degreased (manufactured by Toyo Aluminum Co., Ltd., product name: 8079 material, thickness: 40 μm) was used. (Materials for forming the first corrosion prevention treatment layer (base layer side) and the second corrosion prevention treatment layer (sealant layer side)) As materials for forming the first corrosion prevention treatment layer (base layer side) and the second corrosion prevention treatment layer (sealant layer side), the following (CL-1) and (CL-2) were used. (CL-1): "Sodium polyphosphate stabilized cerium oxide sol" obtained by using distilled water as a solvent and adjusting the solid concentration to 10% by mass. The sodium polyphosphate-stabilized cerium oxide sol was obtained by mixing 10 parts by mass of sodium phosphoric acid with 100 parts by mass of cerium oxide. (CL-2): A composition consisting of 90% by mass of "polyallylamine (manufactured by Nittobo Co., Ltd.)" and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation)" obtained by adjusting the solid content concentration to 5% by mass using distilled water as a solvent.
[0126] <Resin composition for forming adhesive resin layer> As a resin for forming an adhesive resin layer, an adhesive resin (a homopolypropylene (PP)-based acid-modified polypropylene resin composition, manufactured by Mitsui Chemicals, Inc.) was prepared.
[0127] <Resin composition for forming sealant layer> A sealant layer-forming resin composition containing block polypropylene (manufactured by SunAllomer, product name: PC684S) and fatty acid amide as a lubricant was kneaded using a twin-screw extruder to prepare the composition so that the lubricant content was the value shown in Table 1. The unit of the lubricant content in the sealant layer-forming resin composition is "ppm by mass."
[0128] <Composition for forming lubricant layer> A dispersion containing a fatty acid amide (product name: "Fatty Acid Amide E", manufactured by Kao Corporation) and a solvent made of isopropyl alcohol was used as the composition for forming the lubricant layer. The content of the fatty acid amide in the dispersion was set to a concentration of 1.0 mass% in accordance with the target coating amount.
[0129] [Creating exterior materials] (Examples 1 to 5 and Comparative Example 1) First, a first corrosion prevention treatment layer and a second corrosion prevention treatment layer were provided on the metal foil layer in the following manner to form a barrier layer. That is, first, (CL-1) was applied to both sides of the metal foil layer in a dry coating amount of 70 mg / m 2 The layer was then coated by microgravure coating so that the thickness of the layer was 200 mm, and the layer was baked at 200° C. in a drying unit. Next, (CL-2) was applied onto the layer obtained in a dry coating amount of 20 mg / m 2 The coating was performed by microgravure coating so that the thickness of the coating was 100 μm. In this way, composite layers made of (CL-1) and (CL-2) were formed on both sides of the metal foil layer as the first and second corrosion prevention treatment layers, respectively, to obtain barrier layers. These composite layers exhibit corrosion prevention performance by combining the two types of materials, (CL-1) and (CL-2).
[0130] Next, the first corrosion prevention treatment layer side of the barrier layer was attached to the substrate layer by dry lamination using the resin composition for forming the first adhesive layer to obtain a laminate (first laminate) of the barrier layer and the substrate layer. Specifically, a polyurethane adhesive was applied to the surface of the barrier layer facing the first corrosion prevention treatment layer so that the thickness after curing was 5 μm, and the adhesive was dried at 80° C. for 1 minute, and then laminated with the substrate layer and aged at 60° C. for 120 hours to obtain the first laminate.
[0131] Next, the first laminate was set on the unwinding section of an extrusion laminator, and the adhesive resin composition and the resin composition for forming the sealant layer were co-extruded on the second corrosion prevention treatment layer under processing conditions of 270°C and 100m / min to form a heat-sealable resin layer having a thickness of 80μm by laminating the adhesive resin layer and the sealant layer in this order, thereby obtaining a second laminate. At this time, the content of the lubricant in the sealant layer was as shown in Table 1.
[0132] Next, the above-mentioned lubricant layer-forming composition was applied onto the sealant layer of the heat-sealable resin layer of the second laminate such that the amount of the lubricant layer after drying was 30 mg / m2 as shown in Table 1. 2 The lubricant layer was formed by coating so as to obtain a lubricant layer. In this manner, an exterior material (substrate layer / first adhesive layer / barrier layer / thermal fusion resin layer (adhesive resin layer / sealant layer) / lubricant layer) was produced, in which the surface roughness Sa of the surface of the lubricant layer had the value shown in Table 1.
[0133] Comparative Example 2 An exterior material (substrate layer / first adhesive layer / barrier layer / thermal fusion resin layer (adhesive resin layer / sealant layer)) having a surface roughness Sa of the sealant layer having the value shown in Table 1 was produced in the same manner as in Example 1, except that the content of the lubricant in the resin composition for forming a sealant layer was as shown in Table 1 and no lubricant layer was formed on the sealant layer.
[0134] [evaluation] <Moldability> For the exterior packaging materials produced in the Examples and Comparative Examples, the forming limits for deep drawing were determined by the following method, and the formability was evaluated based on the forming limits. First, a rectangular portion measuring 120 mm in the TD direction × 200 mm in the MD direction was cut out as a test sheet from each of the exterior packaging materials obtained in the examples and comparative examples. The test sheet was placed in the molding device so that the lubricant layer or the sealant layer faced upward. The molding depth of the molding device was set to 3.0 to 8.0 mm in increments of 0.5 mm, and cold molding was performed under an environment of room temperature of 23°C and dew point temperature of -35°C. At this time, a punch mold having a rectangular cross section of 70 mm x 80 mm, a punch radius (RP) of 1.00 mm on the bottom, and a punch corner radius (RCP) of 1.00 mm on the side was used. In addition, a die mold having a die radius (RD) of 1.00 mm on the upper surface of the opening was used. In addition, for molding, the test sheet was pressed with a pressing pressure (surface pressure) of 0.8 MPa, and molding was performed on the molding area (TD direction 80 mm x MD direction 70 mm) of half the area of the test sheet (TD direction 120 mm x MD direction 100 mm area). The position of the molding area in the test sheet is as shown in FIG. 4. As shown in FIG. 4, the molding area M is located at a position where the shortest distance from the short side P of the test sheet is 30 mm and the shortest distance from the long side Q of the test sheet is 20 mm. The presence or absence of breaks and pinholes in the pockets formed by molding was visually inspected while shining a light onto the test sheet, and the maximum molding limit (molding depth) at which deep drawing molding could be performed without the occurrence of either breaks or pinholes was determined. The moldability was evaluated based on the moldability limit and the following evaluation criteria. The results are shown in Table 1. (Evaluation Criteria) ◎: Forming limit is 5mm or more ○: Forming limit is 4.0mm or more and less than 5.0mm ×: Forming limit is less than 4.0 mm
[0135] <Effect of preventing battery cells from slipping> Two rectangular test sheets measuring 120 mm in the TD direction and 200 mm in the MD direction were cut out from the exterior packaging materials obtained in the Examples and Comparative Examples. Meanwhile, a Cu foil with long sides of 180 mm, short sides of 100 mm, and a thickness of 2 mm was prepared for use in the negative electrode of the battery cell. The battery cell was then placed between the two test sheets, and a force of 20 kg was applied to the battery cell via the test sheets using two press plates made of stainless steel to prepare a test specimen. While maintaining this state, the test specimen was placed in a vibration tester (product name: "General-purpose vibration tester", manufactured by IMV) and vibrated. After the vibration test, the test specimen was visually inspected to see if the battery cell had moved from the test sheet. The slippage prevention effect of the test sheet on the battery cell was evaluated based on the following evaluation criteria. The results are shown in Table 1. (Evaluation Criteria) ○: The position of the battery cell was not displaced from the test sheet before the test. ×: The battery cell position is misaligned with respect to the test sheet before the test
[0136] <Amount of lubricant layer after storage at 40℃> From the exterior packaging materials obtained in the Examples and Comparative Examples, rectangular sections measuring 120 mm in the TD direction × 200 mm in the MD direction were cut out as test sheets. Then, this test sheet was stored in an environment of 40° C. for 2 weeks (336 hours), and then the amount of the lubricant layer was measured. The amount of the lubricant layer was measured as follows. First, the lubricant layer of the test sheet was washed with chloroform as a solvent for dissolving the lubricant, and the obtained liquid was analyzed by GC-MS to measure the amount of lubricant in the liquid. The amount of lubricant was calculated based on the following formula. The results are shown in Table 1. Amount of lubricant layer (mg / m 2 ) = 100 × measured amount of lubricant (mg) / surface area of the lubricant layer on the test sheet (m 2 )
[0137] [Table 1]
[0138] From the results shown in Table 1, the coating weight of the lubricant layer was 0 mg / m 2 In Examples 1 to 5 and Comparative Example 1, which have more coating amounts, the moldability was rated as ⊚ or ◯, whereas the coating amount of the lubricant layer was 0 mg / m2 In Comparative Example 2, the amount of the lubricant layer after storage at 40°C was 10 mg / m 2 In the following Examples 1 to 5, the lubricant layer had a lubricant suppression effect on the battery cell of 0 mg / m2 or less after storage at 40° C. 2 In Comparative Examples 1 and 2, which had more components, the effect of suppressing slipperiness of the battery cell was rated as "poor." From the above, it has been confirmed that the exterior packaging material for an energy storage device disclosed herein has excellent formability and can suppress slippage against the battery cell even when the battery cell of the energy storage device is placed in an environment of 40°C or higher while being pressurized. [Explanation of symbols]
[0139] Reference Signs List 10, 20... exterior material for electricity storage device, 11... base material layer, 12a... outer adhesive layer, 12b... inner adhesive layer, 13... metal foil layer, 14a... first corrosion prevention treatment layer, 14b... second corrosion prevention treatment layer, 15... adhesive resin layer (heat-sealed resin layer), 16... sealant layer (heat-sealed resin layer), 17... barrier layer, 18... lubricant layer, 50... electricity storage device, 52... battery cell, 53... metal terminal, 54... exterior container.
Claims
1. An exterior packaging material for an electricity storage device, comprising a base layer, a barrier layer including a metal foil layer, and a heat-sealable resin layer in this order, the exterior packaging material comprising: a lubricant layer including a lubricant on a surface of the heat-sealable resin layer; When the electrical storage device packaging material is placed in an environment of 40° C. or higher, the thermal adhesive resin layer takes in the lubricant from the lubricant layer, and the amount of the lubricant layer is 10 mg / m 2 The exterior material for an electricity storage device can be as follows:
2. 2 . The packaging material for a power storage device according to claim 1 , wherein the heat-sealable resin layer includes a sealant layer, and a content of a lubricant in the sealant layer is less than 200 ppm by mass.
3. The packaging material for a power storage device according to claim 1 , wherein the heat-sealing resin layer includes a sealant layer, and the sealant layer includes a polyolefin resin.
4. The exterior material for a power storage device according to claim 1 , wherein the lubricant contained in the lubricant layer is a fatty acid amide.
5. The exterior material for a power storage device according to claim 1 , wherein the lubricant layer is obtained by coating a composition containing the lubricant.
6. 2 . The packaging material for an electricity storage device according to claim 1 , wherein a surface roughness Sa of the surface of the heat-sealing resin layer on the side of the lubricant layer is 1.0 μm or less.
7. The packaging material for an electricity storage device according to claim 1 , further comprising an adhesive layer between the base material layer and the barrier layer.
8. 2 . The packaging material for an electricity storage device according to claim 1 , wherein a static friction coefficient at 60° C. on a surface of the lubricant layer of the packaging material is 0.75 or more.
9. 2 . The packaging material for an electricity storage device according to claim 1 , wherein the lubricant layer of the packaging material has a static friction coefficient of 0.4 or less at 23° C.
10. The exterior packaging material for a power storage device according to claim 1 , wherein the power storage device is an all-solid-state battery.
11. A battery cell; an exterior container that houses the battery cell; The outer container of the power storage device is obtained using the outer packaging material for a power storage device according to any one of claims 1 to 10.
12. The power storage device according to claim 11 , which is an all-solid-state battery.
Citation Information
Patent Citations
External facing material for power storage device
JP2013101765A
Cited By
Terminal film for power storage device and power storage device
WO2026192016A1
Exterior material for electric power storage device, and electric power storage device
WO2026192029A1